EXPERIMENTAL PARTITIONING OF HIGH FIELD STRENGTH AND RARE EARTH ELEMENTS BETWEEN CLINOPYROXENE AND GARNET IN ANDESITIC TO TONALITIC SYSTEMS - AN ION-MICROPROBE STUDY - Klein M.; Stosch H.G.; Seck H.A.; Shimizu N. (My University, 2000)
Partition coefficients of the rare earth elements (REE) and the high field strength elements (HFSE: Ti, Zr, Hf, Nb, Ta) among clinopyroxenes, garnets, and andesitic to granodioritic melts were experimentally determined at pressures ranging from 1 to 3 GPa and temperatures between 900 and 1150°C. Natural rocks of quartz-dioritic and basaltic composition were used as starting materials. Melt compositions covered a range from dioritic to quartz-dioritic and granodioritic. Partition coefficients obtained from experiments with different doping levels at the same run condition indicate that Henry's Law is fulfilled. Partition coefficients were investigated as a function of temperature and phase compositions. Apparent correlations between the clinopyroxene partition coefficients of the REE and degree of depolymerization expressed as nonbridging oxygens per tetrahedron (NBO/T) are due to variations in the Na contents of the clinopyroxenes which are controlled by pressure or NBO/T. Based on the model of Blundy and Wood (1994), which accounts for the strain associated with placing a cation on a particular crystallographic site when the radius of the cation differs from the optimal radius for that site, significant differences between Zr- and Hf partition coefficients as well as correlations between Ti and REE partition coefficients can be explained in terms of differences of their ionic radii. For garnets DLa/DYb ratios change as a function of temperature much more than for clinopyroxenes. This is also consistent with the Blundy and Wood (1994) model.